Study guides

☆☆

Q: What does ab 2a 3b 6 equal using factoring by grouping?

Write your answer...

Submit

Still have questions?

Related questions

(x + 2)(a + b)

2a + a = 3a

3a + 2a = 5a

a + a = 2a

polynomials are problems and factoring is a way to solve them. (2a-1)(8a-5) 16a^2 -10a-8a-5 16a^2 -18a-5

2a2

√20a2b = √4a2 * √5b = 2a√5b the answer is 2a times radical 5b.

The answer is 2a because of the two a's equal 2a

2a + 5a + 3a = 10a

-16A

In order for the formula 3 - 2a = 7 to be solved, the value 2a must equal -4, because 3 - (- 4) = 7. Therefore, a must equal - 2.

(2A/A)+6 is equal to eight. 2A/A leaves one with 2, since the As cancel out and 2 and 6 is eight.

yes! emphatically yes!

this is an expression. if you let it equal something you can find (a)2a + 8 = 4a = -2or you could do2a + 8 = 106a = 49It is 2a + 8.

a times 2 equals 2a

2a+2b+3a+3b+a+b= 6a+6b 2a+3a+a=6a 2b+3b+b=6b

a2 + 2a - 3 = 0(a + 3)(a - 1)a = - 3a = 1Simple factoring where you ask yourself; what two factors of - 3 add up to 2?

The answer of the equation 2a -46a plus 252 = 0 using the quadratic formula is a = 5.25.

We have the algebraic expression: 8a2 - 2aIn order to factorize it, we can just simply pull out 2a and we are now left with this: 2a(4a-1)But, why 2a?In the given algebraic expression we have two terms: 8a2 and -2aNow, we have to look for the common factor of 8a2 and -2a.8a2 = 8 x a x a = 2 x 2 x 2 x a x a-2a = -2 x aCommon factor is 2a. (2 is also the common factor but we need greatest common factor which is 2a)4a - 1 can not be further factorized so the final answer is 2a(4a-1).Visit the link provided below to learn more about factoring.

It is: (2*3)+5 = 11

2a + 4b + 8c = 2(a + 2b + 4c) You could also continue by factoring the inside of the parentheses a bit: 2a + 4b + 8c = 2(a + 2b + 4c) = 2(a + 2[b + 2c])

No. 2a is one thing, 3b is another. If you add them together, they become 2a + 3b. 5ab indicates that multiplication has taken place. 5 times a times b = 5ab

I'm assuming you are talking about this equation:x = [ -b +|- sqrt ( b2 - 4ac ) ] / ( 2a )where, ax^2 + bx + c = 0The formula is called the quadratic formula. It is used when either factoring is too difficult/tedious or for complex numbers.

A + 2a = 3a

A+c= 2a+b